Urbanization, Oil Price and Pollution in Saudi Arabia - Mahmood, Haider; Alkhateeb, Tarek Tawfik Yousef; Al-Qahtani, Maleeha Mohammed Zaaf; Allam, Zafrul; Ahmad, Nawaz; Furqan, Maham (International Journal of Energy Economics and Policy, 2020)
Urbanization and income are usually supported by oil prices and revenues in the oil abundant countries. But, the environmental effect of urbanization and oil prices should not be ignored to ensure the sustainable growth of oil abundant economies. We investigate the role of urbanization and oil prices on the CO2 emissions per capita of Saudi Arabia using a period 1980-2014 and cointegration test. Urbanization has positive on the CO2 emissions per capita. So, a rapid and continues increasing urbanization throughout the sample period is found responsible for degrading the environment. Moreover, the oil price is also found responsible for increasing CO2 emissions in the long run but its effects are found insignificant in the short run. We recommend the Saudi economy to diversify from the oil sector to ensure clean environment. Keywords: CO2 emissions, Oil prices, Urbanization, Cointegration JEL Classifications: Q53, P25, Q34 DOI: https://doi.org/10.32479/ijeep.8914